5
$\begingroup$

This is a challenge problem in the Pell Equations chapter of my number theory book, but I'm not seeing the connection to Pell Equations. The Pell Equation with the coefficient $5$ is $5b^2+1=a^2$, but it doesn't look like the one I have.

Thanks if you can help me.

$\endgroup$
  • 2
    $\begingroup$ The connection is similar to that of homogeneous and in-homogeneous linear equations, but instead of adding you multiply. If you have a solution of your equation $a^2-5b^2=-4$ and solutions of $A^2-5B^2=1$ then you can multiply the two equations $-4=-4\cdot1=(a^2-5b^2)(A^2-5B^2)=(aA+5bB)^2-5(bA+aB)^2$ andget more solutions of your equation. $\endgroup$ – Carol Feb 10 '15 at 18:41
  • $\begingroup$ @Carol: Sorry if I didn't understand something, but my equation is $a^2-5b^2=-4$ not $a^2-5b^2=4$. Thanks for your reply! $\endgroup$ – user45220 Feb 10 '15 at 18:44
  • $\begingroup$ I missread. But it is the same idea. Just put a $-4$ where I wrote $4$. $\endgroup$ – Carol Feb 10 '15 at 18:45
  • $\begingroup$ maybe help :$$a^2+4=5b^2\\a^2-b^2=4b^2-4\\(a-b)(a+b)=4(b^2-1)\\(a-b)(a+b)=4(b-1)(b+1) $$ $\endgroup$ – Khosrotash Feb 10 '15 at 18:54
  • 1
    $\begingroup$ see math.stackexchange.com/questions/742181/… $\endgroup$ – Will Jagy Feb 10 '15 at 19:36
2
$\begingroup$

if a,b are natural numbers :$$a-b<a+b\\(a-b)(a+b)=4(b-1)(b+1)=\\1*(4(b-1)(b+1)\\=2*2(b-1)(b+1)\\=(b-1)*(4(b+1)\\=(b+1)*(4(b-1))\\=2(b-1)*(2(b+1))$$now try them to get answer

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

I know full well the problem was asked and answered 3 years ago. Yet I wish to contribute. Please critique and comment so I learn something.

$$\begin{align} a^2+4&=5b^2 \\ a^2-5b^2&=-4 \quad \text{initial solution} \quad (a_1, b_1) =(1,1)\\ (a-b \sqrt5)(a+b \sqrt 5)&=-4\\ \text{since} \quad &(1-\sqrt 5)(1+\sqrt 5)=-4 \\ \text{then} \quad &(1-\sqrt 5)^2(1+\sqrt 5)^2=(-4)^2 \\ &(6-2 \sqrt 5)(6+2 \sqrt 5)=4^2 \quad \text{and}\\ (a-b \sqrt5)(6-2 \sqrt 5)(a+b \sqrt 5)(6+2 \sqrt 5)&=-4^3\\ (6a+10b)^2-5(2a+6b)^2&=-4^3 \\ \left(\frac{3a+5b}{2}\right)^2-5\left(\frac{a+3b}{2}\right)^2&=-4 \implies\\ &\begin{cases} a_{k+1}=\frac{1}{2}(3a_k+5b_k) \\ b_{k+1}= \frac{1}{2}(a_k+3b_k)\end{cases}\\ &\implies \\ &(1,1) \to (4,2) \to (11, 5) \to (29, 13) \to \cdots \end{align}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.